2015
DOI: 10.1039/c4nr05717a
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquid-modulated preparation of hexagonal tungsten trioxide mesocrystals for lithium-ion batteries

Abstract: Hexagonal (h-WO3) mesocrystals with biconical morphology were prepared by a straightforward ionic liquid-assisted hydrothermal route and investigated as anodic materials for lithium-ion batteries. Compared to the alternatives, the biconical tungsten trioxide mesocrystal exhibited excellent lithium insertion with good cyclability and rate capability, making it a promising candidate as the anode material for high-performance lithium-ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 51 publications
1
28
0
Order By: Relevance
“…Duan et al preparedh -WO 3 mesocrystals with different morphologies and crystal structures through an ionic-liquid-assisted hydrothermal method for LIBs. [160] The h-WO 3 biconical mesocrystalline electrode exhibited ab etter electrochemical performance than that of ar od-like single-crystalline electrode and polycrystallinee lectrode. The h-WO 3 biconical mesocrystalline electrode demonstrated first discharging and charging capacities of 1379a nd 1216 mAh g À1 ,r espectively,a t5 0mAg À1 , and maintained av alue of 426 mAh g À1 over 50 cycles.…”
Section: Current Advances In Wo 3 -Based Batteriesmentioning
confidence: 93%
See 1 more Smart Citation
“…Duan et al preparedh -WO 3 mesocrystals with different morphologies and crystal structures through an ionic-liquid-assisted hydrothermal method for LIBs. [160] The h-WO 3 biconical mesocrystalline electrode exhibited ab etter electrochemical performance than that of ar od-like single-crystalline electrode and polycrystallinee lectrode. The h-WO 3 biconical mesocrystalline electrode demonstrated first discharging and charging capacities of 1379a nd 1216 mAh g À1 ,r espectively,a t5 0mAg À1 , and maintained av alue of 426 mAh g À1 over 50 cycles.…”
Section: Current Advances In Wo 3 -Based Batteriesmentioning
confidence: 93%
“…Duan et al. prepared h‐WO 3 mesocrystals with different morphologies and crystal structures through an ionic‐liquid‐assisted hydrothermal method for LIBs . The h‐WO 3 biconical mesocrystalline electrode exhibited a better electrochemical performance than that of a rod‐like single‐crystalline electrode and polycrystalline electrode.…”
Section: Current Advances In Wo3‐based Batteriesmentioning
confidence: 99%
“…Yoshio and co‐workers synthesized WO 3 hollow spheres with high lithium‐storage capacity and good cyclability, showing a high charge/discharge capacity of 327/332 mA h g –1 at a charge/discharge 0.2 C after 50 cycles ( Figure a) . Wang and co‐workers reported that WO 3 meso­crystals maintain a reversible capacity of 426 mA h g –1 after 50 cycles at a current density of 0.4 C . Kang and co‐workers synthesized yolk–shell WO 3 particles with a high discharge capacity of 556 and 523 mA h g –1 after 30 and 120 cycles, respectively, at a current density of 0.4 C (Figure b) .…”
Section: Tungsten Oxides For Electrochemical and Photoelectric Applicmentioning
confidence: 99%
“…A stable and spinnable precursor solution was first formulated by employing an IL, 1‐ n‐butyl ‐3‐methylimidazolium dihydrogenphosphate ([Bmim]H 2 PO 4 ), as phosphate source in the PAN‐based solution . In the subsequent electrospinning process (Figure S1), the anion of IL participated the formation of LFMP, the imidazole cation was in situ adsorbed on the formed nanoparticle surface due to electrostatic attraction, similar to the classic Dergaugin–Landau–Verwey–Overbeek (DLVO) type coulombic repulsion model (Figure a) . After the high‐temperature carbonization, the surface attached IL transformed to N‐doped carbon layer coating, accompanied by the formation of macroporous structure around LFMP nanoparticles.…”
Section: Figurementioning
confidence: 99%